IMPLEMENTASI DAN ANALISA MIKROTIK CLOUD SMART SWITCH PADA JARINGAN INTERNET DI UNIVERSITAS BENGKULU - Prasetya, Anjas Mara; Kalsum, Toibah Umi (UNIVED Press, 2021)
This research aims to implement the Mikrotik cloud smart switch on the internet network at Bengkulu University, increase the effectiveness of device performance on the internet network, find out the factors that influence the performance of the Mikrotik cloud smart switch, make it easy for network admins to control each Cloud SmartSwitch installed on each Bengkulu University building. The research method used is action research, which is a research method that will be achieved and ended not only in certain organizational situations, but will continue to be developed in the form of applications or theories and then the results will be published to the public for research purposes. Based on the results of testing and analysis after going through various processes in implementing the Mikrotik Cloud Smart Switch on the internet network at Bengkulu University, the system on the Mikrotik Cloud Smart Switch was successfully implemented, the internet network at Bengkulu University is more stable and makes it easier for network admins to manage and monitor Mikrotik activities. cloud smart switch.